Photo-essay and Adult Immigrants’ Identities and Agency - Kay Yang (Adult Education Research Conference, 2019)
Drawing on a photo-essay creation project conducted with a group of adult immigrants in a metropolitan area, I explore how the visual method can contribute to their identity construction and empowerment and question how we know.
Keywords: Photo-essay; immigrant; identity; agency; visual method